FILOSOFIS KOMUNIKASI QAULAN SYAKILA - Fahriansyah, Fahriansyah (UIN Antasari Banjarmasin, 2018)
The principles of comunication in the Qur?an are interesting to examine, even the comunications thinkers have found there are six principles of comunication in al qur?an such as qawlan sadidan, qawlan balighan, qawlan maysura, qawlan layyinan, qawlan kariman and qawlan ma?rufan, but the opinion can be added again one principle that is qawlan tsaqila principle that is a weighted communication, then what and how qawlan tsaqila ?, this paper will explain briefly iti is in addition to the six principles of comunication in al Qur?an put forward by the communications leaders muslim Indonesia.